Correction: Influence of carbonization conditions on luminescence and gene delivery properties of nitrogen-doped carbon dots. Issue 14 (7th March 2019) - Claudel, Mickaël; Fan, Jiahui; Rapp, Mickaël; Pons, Françoise; Lebeau, Luc
Abstract : Correction for 'Influence of carbonization conditions on luminescence and gene delivery properties of nitrogen-doped carbon dots' by Mickaël Claudel et al., RSC Adv., 2019, 9, 3493–3502.